2011
DOI: 10.1007/s11250-011-9973-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on preweaning performance of Sahiwal calves

Abstract: The objective was to study the growth potential of Sahiwal calves given milk or milk replacer with or without concentrates. For this purpose, forty-eight Sahiwal calves were divided into four groups of 12 animals each with equal sex ratio. In each group, the calves were offered either milk or a milk replacer (MR) at a rate of 10% of their body weight adjusted weekly. In addition to this, calves were fed either a starter ration plus Egyptian clover hay (SR + H) or hay only (H) until the end of trial. The milk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…An initial challenge faced was separating buffalo calves from their dams and weaning them onto artificial feeding through nipples. Feeding buffalo calves through nipples was more difficult than Sahiwal cow calves raised previously (Bhatti et al 2012a(Bhatti et al , 2013 in separate experiments. During the current trial, two of the buffalo calves did not accept nipple feeding until the end of the experiment and thus were removed from the study.…”
Section: Milk Intakementioning
confidence: 95%
See 1 more Smart Citation
“…An initial challenge faced was separating buffalo calves from their dams and weaning them onto artificial feeding through nipples. Feeding buffalo calves through nipples was more difficult than Sahiwal cow calves raised previously (Bhatti et al 2012a(Bhatti et al , 2013 in separate experiments. During the current trial, two of the buffalo calves did not accept nipple feeding until the end of the experiment and thus were removed from the study.…”
Section: Milk Intakementioning
confidence: 95%
“…Thus, feeding strategies are required to reduce the cost of rearing buffalo calves to weaning. Early weaning of Sahiwal calves and offering them solid feed or using milk replacer reduced preweaning feeding costs, however, this practice resulted in poor weight gains at weaning (Bhatti et al 2012a). However, Rashid et al (2013) reported that buffalo calves can be weaned successfully at 8 weeks without compromising their growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…Before weaning, they had been a part of a two by two factorial pre-weaning feeding trial reported by Bhatti et al (2011). The two factors were -liquid feed (milk or MR) and solid feed (starter concentrate ration with H or H only).…”
Section: Methodsmentioning
confidence: 99%
“…During the pre-weaning period, initially there were 12 calves in each group with six of each sex; however, one male calf died from each of the B and C treatments and were not replaced. Thus, 46 calves were assigned to the current post-weaning study, comprised of 12, 11, 11 and 12 calves from the original pre-weaning groups A, B, C and D, respectively, as described by Bhatti et al (2011). During the post-weaning period, after 84 days of age, the calves were given a single TMR (Table 1) Feeding and housing Animals were housed in separate calf pens (142 3 112 3 112 cm: L 3 W 3 H).…”
Section: Methodsmentioning
confidence: 99%
“…Studies carried out in tropical areas show low average daily gain of calves (Bhatti et al 2012;Das et al 2000). However, the lactation curve of Zebu cows allows the adoption of different management strategies (Santos et al 2014), since their reduced milking period allows the milk produced in late lactation to be consumed by the calves resulting in higher weaning weights.…”
Section: Nutrients Intake By Calves and Performancementioning
confidence: 99%